Perlindungan Hukum Terhadap Keluarga Tersangka Tindak Pidana Korupsi Dari Dampak Perampasan Aset Ditinjau Berdasarkan Kajian Pasal 34 UUD 1945 - Murry Mirranda; Aarce Tehupeiory (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
In Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, Corruption can be categorized into seven types, namely 1) state financial losses; 2) bribery; 3) extortion; 4) embezzlement in office; 5) fraud; 6) conflict of interest in the procurement of goods and services; and 7) gratification. The construction of the criminal law system, especially regarding corruption, which has been developed recently in Indonesia still aims to uncover crimes that have occurred, find the perpetrators and punish the perpetrators of criminal acts with criminal sanctions, especially "corporal punishment" both imprisonment and detention. Meanwhile, the issue of legal development in the international scope such as the issue of confiscation and confiscation of proceeds of crime and instruments of crime has not become an important part of the criminal law system in Indonesia. In its implementation, the phenomenon of confiscation of assets in corruption cases often has an impact on the families of innocent perpetrators, espe The method used in this paper is juridical-normative, with a conceptual and philosophical approach, reinforced by empirical studies at the implementation stage. The type of data used is secondary data sourced from primary, secondary and tertiary legal materials. Furthermore, the data collection technique in this study was conducted through library research. The data was then analyzed qualitatively using descriptive-analytical techniques.The study found that the forms of legal and state protection in protecting the families of corruption suspects from the impact of asset confiscation are very complex and not yet fully regulated in Indonesian law. However, the concept of protecting basic family rights is implied in the principle of the rule of law, as stated in Article 34 of the 1945 Constitution, which explicitly links the state's responsibility to vulnerable citizens, such as the poor and neglected children, through three main articles: caring for the poor and neglected children, developing a social security system, and providing adequate health care facilities and public services for all.